STUDY OF PEDAGOGY AND PEDAGOGICAL DISCIPLINES IN EDUCATIONAL INSTITUTIONS OF THE ORTHODOX CHURCH: VIEWS OF EDUCATORS AND THEOLOGIANS (the end of the 19th century – the beginning of the 20th century) - Tverdokhlib, Tetiana (Educological discourse, 2019)
Based on the analysis of primary sources and historical-pedagogical literature, the article presents educators and theologians’ views on teaching Pedagogy and pedagogical disciplines in educational institutions of the Orthodox Church during the second half of the 1890s – 1918. These educators and theologians are Archimandrite Vissarion, I. Andreiev, D. Briantsev, A. Hrynevych, G. Maliarevskyi, M. Makkaveiskyi, P. Sokolov, N. Krasovskyi, A. Yurykas and others. It has been determined that theoretical ideas about the outlined problems were presented in publications in theological periodicals (such as “Theological Herald”, “Faith and Reason”, “Volyn Diocesan Information”, “People’s Education”, “Podillya Diocesan Information”, “Christian Reading”, “Church Herald”, “Chernihiv Diocesan Information” etc.). The article reveals the educators’ and religious leaders’ ideas about the tasks of pedagogical training, content, organizational aspects, forms and staffing for teaching Pedagogy and pedagogical disciplines in Orthodox theological academies, seminaries, women’s educational institutions of the Orthodox Church, church-teacher schools and second-degree schools. It has been determined that the scientists again paid attention to certain problems that were of scientific interest for educators and theologians in 1860-1870s.